Designing a Credit Submission System Using Android Online-Based SAW Methods - Kevin Kevin; Wenne Ramly (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2019)
Credit is a financial facility that allows a person or business entity to borrow money to buy a product and repay it within a specified period of time. PT. Capella Multidana is a consumer goods financing company, especially for other vehicle products with the largest and largest outlet network in Indonesia. The number of those who apply for credit makes the company difficult and the process is long because the process with the decision by means of a recording system to determine the right according to the criteria that have been determined. Based on the results of the study, it was concluded that the PT. Capella Multidana consists of several procedures, namely credit applications, credit investigation and analysis, credit approval, credit disbursement, and credit repayment. The credit application system of PT. Capella Multidana has been effective, each unit or division has clear duties and authority, making it easier for employees to do their jobs properly and well.